FRANKENSTEIN - Shelley, Mary, (Shelley, Mary Wollstonecraft) 1797-1851.; Roche, Ruth A. (Ruth Ann), 1921-1983.; Brewster, Ann; Webb, Bob, 1915-2000 (Newbury, Berkshire : CCS Books, 2016)
CLASSIC FICTION (CHILDREN'S / TEENAGE). Dr. Victor Frankenstein's life's work is to re-animate the recently deceased, however when he finally achieves his goal, things do not quite work in the way he had hoped...Classics Illustrated tells this wonderful tale in colourful comic strip form, offering an excellent introduction for younger readers. This edition also includes a biography of Mary Shelley, theme discussions and study questions, which can be used both in the classroom and at home to further engage the reader in the work at hand.
Primary.
Keywords: Frankenstein, Victor (Fictitious character) -- Comic books, strips, etc.|; Monsters -- Comic books, strips, etc; Children's stories -- Comic books, strips, etc; Graphic novels; Comics adaptations